Recent longitudinal evidence of size and union threat effects across genders - Phanindra V. Wunnava (Institute for the Study of Labor (IZA), 2012)
Based on data from the National Longitudinal Surveys of Youth covering years 2000 through 2008, it is evident that both male and female workers in medium/larger establishments receive not only higher wages but also have a higher probability of participating in benefit programs than those in smaller establishments. This reinforces the well-documented 'size' effect. Further, the firm size wage effects are much larger for men than women. The union wage effect decreases with establishment size for both genders. This supports the argument that large nonunion firms pay higher wages to discourage the entrance of unions (i.e., the 'threat' effect argument). In addition, the union wage premium is higher for males for small and medium firm sizes relative to females. This implies that unions in the large establishments may have a role to play in achieving a narrowing of the gender union wage gap. In other words, the threat of unionization could reduce union wage premiums for both genders as firm size increases. Given the presence of noticeable gender differences in estimated union effects on the different components of the compensation structure, unions should not treat both genders similarly with respect to wages and benefits.
Keywords: J16; J31; J32; J51; 330; size effect; threat effect; random effects; fringe benefits; compensation; gender; union-nonunion